Limnología de la Presa Melchor Ocampo, Municipio de Angamacutiro, Michoacán - Medina Ávila, Julio César (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
Limnology is the discipline of scientific knowledge oriented to the study of the structure and function of the epicontinental waters of the planet (Wetzel, 1983; Hutchinson, 1967 and Ruttner, 1963). This includes both natural systems such as lakes, lagoons, springs, rivers, streams and wetlands, as well as man-made artificial systems including dams, ponds and canals. Limnology in Mexico has shown a growing trend towards the development of research and knowledge generation on the structure and function of national aquatic ecosystems, however, this scientific discipline requires greater spatial coverage to include as a study object all the epicontinental systems of the country in addition to achieving a multidisciplinary integration. For centuries, the lakes and reservoirs of Mexico have represented strategic areas for the development of different civilizations, both pre-Hispanic and current society, not only because fresh water has been an important source of food but also because it is a basic resource for the sustenance of various economic activities that are part of national development. To the above is associated the natural beauty of these aquatic systems and their impact on tourism and recreational activity, as well as the environmental function they play in the hydrological cycle, the maintenance of the climate and the ecological balance.

La limnología es la disciplina del conocimiento científico orientada al estudio de la estructura y función las aguas epicontinentales del planeta (Wetzel, 1983; Hutchinson, 1967 y Ruttner, 1963). Lo anterior incluye tanto a los sistemas naturales como los lagos, lagunas, manantiales, ríos, arroyos y humedales, como a los sistemas artificiales construidos por el hombre incluyendo a las presas, estanques y canales. La limnología en México ha manifestado una tendencia creciente hacia el desarrollo de la investigación y generación de conocimientos sobre la estructura y función de los ecosistemas acuáticos nacionales, sin embargo, esta disciplina científica requiere una mayor cobertura espacial para incluir como objeto de estudio la totalidad de los sistemas epicontinentales del país además de alcanzar una integración multidisciplinaria. Durante siglos los lagos y embalses de México han representado zonas estratégicas para el desarrollo de las diferentes civilizaciones tanto aquellas prehispánicas como la sociedad actual, no solamente porque el agua dulce ha sido una importante fuente de alimento sino porque es un recurso básico para el sustento de diversas actividades económicas que forman parte del desarrollo nacional. A lo anterior se asocia la belleza natural de estos sistemas acuáticos y su impacto en la actividad turística y recreativa, así como la función ambiental que desempeñan en el ciclo hidrológico, el mantenimiento del clima y el equilibrio ecológico.
Instituto de Investigaciones sobre los Recursos Naturales. Maestría en Ciencias en Limnología y Acuicultura
Keywords: info:eu-repo/classification/cti/2; INIRENA-M-2008-0002; Presa Melchor Ocampo; Angamacutiro; Michoacán; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5775